2003
DOI: 10.1785/0120020205
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Q-Values in the Seismogenic and Aseismic Layers in the Kinki Region, Japan, by Elimination of the Geometrical Spreading Effect Using Ray Approximation

Abstract: The Q-value is one of the parameters controlling attenuation of seismic waves with distance. Attenuation relations in crust used in the earthquake engineering applications usually consider models with uniform Q and geometrical spreading. In this work we try to estimate a nonuniform Q-value based on the ray geometrical spreading in a nonuniform velocity model. We estimate Q-values in the seismogenic and aseismic zones of the Kinki region (Japan) using Hi-net data. The Hi-net network consists of high-sensitivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Salah and Zhao 2003a), and (3) the OBS velocity models. The Q-structure is similar to that of Salah and Zhao 2003b), and is slightly modified according to the results of Petukhin et al 2003Petukhin et al , 2007 In the subducting area, the accretion prism or the sedimentary wedge is observed in the cross sections of the exploration surveys (e.g., Kodaira et al 2002, Nakanishi et al 1998, 2002. The thickness of these sediments appears to be several kilometers, and this strongly affects the results of ground motion simulations for subduction events (e.g.…”
Section: Crustal Velocity Structure Modelmentioning
confidence: 69%
See 1 more Smart Citation
“…Salah and Zhao 2003a), and (3) the OBS velocity models. The Q-structure is similar to that of Salah and Zhao 2003b), and is slightly modified according to the results of Petukhin et al 2003Petukhin et al , 2007 In the subducting area, the accretion prism or the sedimentary wedge is observed in the cross sections of the exploration surveys (e.g., Kodaira et al 2002, Nakanishi et al 1998, 2002. The thickness of these sediments appears to be several kilometers, and this strongly affects the results of ground motion simulations for subduction events (e.g.…”
Section: Crustal Velocity Structure Modelmentioning
confidence: 69%
“…Figure 2 shows a schematic cross-section of the crustal velocity structure model that includes the subducting Philippine Sea slab in the Kinki area. It reflects the main principles of velocity modeling, developed by Petukhin et al (2003) and Iwata et al (2006). They are: (1) intensive use of the OBS velocity models in offshore areas for the accretion prism, or the sedimentary wedge, and oceanic crust modeling; (2) employing seismicity data for tracing the seismogenic slab and seismogenic upper crust; (3) intensive use of the receiver function inversion results for tracing Moho, and Conrad and slab in the aseismic areas; (4) employing deep seismic profiling results for inland areas whenever possible; and (5) employing 1D velocity models used for the hypocenter locations and generalized seismic tomography results for the remaining areas not covered by the data.…”
Section: Crustal Velocity Structure Modelmentioning
confidence: 99%
“…The 3‐D Q P and Q S models determined in this study can similarly be used in earthquake hazards calculations, although an appropriate calibration will be needed. In particular, trade‐offs between parameters in 3‐D models may exist; for instance, the frequency content of the waves used here and assumed geometrical spreading factors may differ from past studies [ Frankel et al , 1990; Petukhin et al , 2003]. Comparison with results from forward waveform modeling also should be done with care because most waveform modeling is done at lower frequencies than used in our study [e.g., Olsen et al , 2003].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, we seek to identify the spatial extent of low or high Q zones or if anomalous regions of high or low Q exist at depth that can be associated with past tectonic history or zones of anomalous temperatures. The brittle‐ductile transition could spatially coincide with changes in the material composition or temperature, which may be imaged as sudden changes in Q with depth [ Petukhin et al , 2003]. Similarly, we are interested in understanding if attenuation losses are significantly different in the reflective lower crust as compared to the upper crust.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies determined Q(f) for Japanese regions (Kinoshita, 1994;Moya and Irikura, 1998;Moya et al, 2000;Petukhin et al, 2003). We have chosen two definitions to compare their influence on the path-effect correction and ascertain whether a precise determination was needed.…”
Section: Path Effect Correctionsmentioning
confidence: 99%